2020
DOI: 10.5658/wood.2020.48.1.95
|View full text |Cite|
|
Sign up to set email alerts
|

Insect Repellency and Crop Productivity of Essential Oil Films

Abstract: The purpose of this study was to determine the effects of coniferous essential oils (EOs) blended films on insect repellence and crop productivity. Low-density polyethylene (LDPE) film is widely used, especially in agriculture and for food packaging. Ethylene vinyl acetate was blended with LDPE to reduce volatilization of EOs. An EO from Japanese cypress (Chamaecyparis obtusa) was incorporated into the blend film to conduct field research on antimicrobial and insect repellent properties. Among the various conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…obtusiloba inhibited airway inflammation in a murine model of ovalbumin (OVA)-challenged asthma, suggesting that it may have possible applications in allergic diseases, such as asthma and atopic dermatitis (Lee et al, 2020) was shown that the mucin-inhibitory effect of L. obtusiloba EO was superior to that of the extract. However, the effects of L. obtusiloba oil and the active components have not been reported.…”
Section: Effects Of Essential Oils (Eos) On the Mucin Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…obtusiloba inhibited airway inflammation in a murine model of ovalbumin (OVA)-challenged asthma, suggesting that it may have possible applications in allergic diseases, such as asthma and atopic dermatitis (Lee et al, 2020) was shown that the mucin-inhibitory effect of L. obtusiloba EO was superior to that of the extract. However, the effects of L. obtusiloba oil and the active components have not been reported.…”
Section: Effects Of Essential Oils (Eos) On the Mucin Gene Expressionmentioning
confidence: 99%
“…The Evaluation of Anti-Asthmatic Activity of Essential Oils from the Lauraceae Family in Lipopolysaccharide (LPS)-Stimulated NCI-H292 Cells EO is one of the secondary metabolites derived from aromatic plants, and it consist of volatile compounds (Ham et al, 2020). The EOs can relieve certain symptoms including anxiety, pain, insomnia, and bacterial infections (Ali et al, 2015;Kim et al, 2020). It is known to have bioactivities such as anti-fungal, antiinsect, anti-bacterial, and anti-inflammatory, and antioxidant activities (Jang et al, 2012;Lee et al, 2014;Pujiarti and Kasmudjo, 2016;Yang et al, 2019;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most mixtures of insecticides and biopolymers for agricultural applications are micro or nanocapsules spread on crops. ,,, Nowadays, there is growing interest in the idea of incorporating active substances into plasticulture to develop a new physical−chemical barrier against insects. Therefore, some studies investigated the use of insecticide-treated nets and insect-repellent films as mulch or greenhouse cover materials with promising results. However, there has only been limited work on the incorporation of active substances against insects in plasticulture, and most of them rely on chemical pesticides , and petropolymers, , which is not a sustainable solution for crop protection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some studies investigated the use of insecticide-treated nets and insect-repellent films as mulch or greenhouse cover materials with promising results. However, there has only been limited work on the incorporation of active substances against insects in plasticulture, and most of them rely on chemical pesticides , and petropolymers, , which is not a sustainable solution for crop protection. Thus, it is crucial to develop a new solution to control aphids that excludes the use of chemical pesticides and overcomes the drawbacks of botanical pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Among variable wood species, the Hinoki cypress (Chamaecyparis obtusa) is a helpful tree for human health (Fujimoto et al, 2021;Kim et al, 2020;Yang et al, 2019;Yeon et al, 2019). Li et al (2009) reported an improvement in immune system function markers in subjects exposed to Hinoki cypress (Chamaecyparis obtusa) and Japanese cedar (Cryptomeria japonica).…”
Section: Introductionmentioning
confidence: 99%